Letter (copy) : Grant - International Solidarity Fund - Citrine, Walter, 1887-1983
034-0131-001 Secretary's. WMC/HVT/FC/24. RP/HH. 7th October, 1938. Mr. R. Prain, The Electrical Trades Union, 11, Macaulay Road, Clapham Common, S.W.4. Dear Mr. Prain, GRANT - INTERNATIONAL SOLIDARITY FUND. I desire to acknowledge receipt of your letter of no date which was received about a week ago on the above subject. The position is not quite as stated in your letter. The International Solidarity Fund being raised in this country for Spain is for the Spanish workers. Consideration will, however, again be given to the question of support of the International Brigade Dependants and Wounded Aid Committee when certain particulars asked for have been received. Under the circumstances we thought it best to endorse your cheque and forward it to the Committee as a contribution from your Union Yours sincerely, General Secretary. P.S. I am enclosing the receipt for £100 which has just been received from the International Brigade Dependants and Wounded Aid Committee. 292/946/34/131